Chronic hepatitis E infection in children with liver transplantation. Issue 4 (23rd November 2011) - Halac, Ugur; Béland, Kathie; Lapierre, Pascal; Patey, Natacha; Ward, Pierre; Brassard, Julie; Houde, Alain; Alvarez, Fernando
Abstract : Objective: Chronic hepatitis E virus (HEV) infection has been described in immunosuppressed adult patients. A study was undertaken to establish the presence of HEV infection in children after orthotopic liver transplantation (OLT). Methods: Children undergoing liver transplantation between 1992 and 2010 with available serum were classified into two groups: group 1 (control group, n=66) with normal serum aminotransferases and group 2 (n=14) with persistently increased serum aminotransferases and histological features of chronic hepatitis. Patients were tested for HEV RNA by reverse transcription-polymerase chain reaction (RT-PCR). HEV amplicons were sequenced and compared with published sequences. Antibody titres (IgG and IgM) to 12 HEV immunodominant regions were measured by enzyme-linked immunosorbent assays. Results: In group 1 (control group), 15% of children were anti-HEV IgG-positive during follow-up. No anti-HEV IgM antibodies were detected in any of these children. After OLT, 86% of patients in group 2 had anti-HEV IgG compared with 36% pre-OLT. Thus, two-thirds of children acquired anti-HEV IgG after OLT. Seven anti-HEV IgG-positive patients (58%) were also anti-HEV IgM-positive more than once during follow-up after OLT. Eight years post-OLT, one girl presented with anti-HEV IgG and IgM that remained positive afterwards. In this patient, HEV RNA was found in five different annual samples from 10 years post-OLT, concomitantly with increased serum aminotransferases and cirrhosis development during that period. Phylogenetic analysis revealed two different HEV strains (detected 3 years apart) that were highly similar to swine genotype 3, suggesting a possible case of zoonotic re-infection. Conclusion: The diagnosis of HEV infection is technically challenging and should be made simultaneously with RT-PCR methods, viral load quantification and serological markers. In immunosuppressed children who develop chronic hepatitis, the prevalence of HEV is high and could explain the chronic liver inflammation potentially leading to cirrhosis. Re-infection by different HEV strains from zoonotic transmission can result in progressive liver disease in immunocompromised children.